Contemporary threats to professional sport resulting from beginning specialist training too early - Umiastowska, D.; Domanska, U. (Journal of Kinesiology and Exercise Sciences, 2019)
Introduction. Professional sport aims at the highest feat forcing players to achieve such a form guaranteeing victory. The career of a young athlete and focus on strict sports specialisation starts very early. The threat to professional sport comes from technological progress and the lack of natural, general forms of activities in the early school period, and resulting in movement pattern disorders and compensations resulting from them. Aim. Presentation of contemporary threats to professional sport resulting from the early implementation of sport specialisation. Research materials and methods. The research material is a group of 60 girls and 60 boys (15-19 y.o.) attending sports schools in the West Pomeranian voivodeship. The research was carried out in the period from 2015-2019 by means of questionnaire implementation. Results. The respondents declared lack of movement and general development activities in the early school period. Very early direction towards a particularly chosen sport caused a number of dysfunctions of the movement apparatus and influenced the occurrence of injuries and breaks in sports training. Moreover, it caused early termination of sports career among 70% of players. The exceptions were swimmers and water rescue participants. Conclusions. 1. Among the examined girls and boys, there was a regression in the continuation of sports career by young people attending sports schools. 2. The reason for the early completion of sports training may be the lack of movement and general development training in the early school period, and sports specialisation began far too early.